The Issues of Commercial Arbitration in Investment Disputes: A Comparative Study - Abed, Raghad Fawzi (International Journal of Psychosocial Rehabilitation, 2020)
The legislation places some restrictions on the entry of investment into the national territory, such as limiting vital areas of investment to the state only. Countries seek to attract these foreign investments by granting many advantages and legal guarantees. Commercial arbitration is one of these guarantees mentioned by the Iraqi legislator in the Investment Law No. 13 of 2006 amending, by allowing the investment dispute to be referred to a national or foreign arbitration body agreed upon by the parties. It is well known that arbitration is an optional judiciary, and it is a means of settling disputes or settling them without resorting to the national judiciary. The importance of the study lies in the fact that the continuous endeavor of the state after 2004 to attract the largest possible amount of foreign investment necessitates addressing one of the guarantees of the expansion of the investment area within it by stating the most important guarantees provided by the law, which are commercial arbitration. In addition, the research aims to clarify the obstacles that surround commercial arbitration in Iraq and the reasons that prevent the existence of reliable national arbitration bodies and resort to them when a dispute occurs between the investing party and the corresponding party in the investment contract. The results show that arbitration is a system of private litigation whereby the parties to the dispute agree to refer their dispute to the arbitrators in a dispute already or in the future to settle it outside the scope of the ordinary court. Commercial arbitration has many advantages that encourage investors to resort to it to settle their disputes. In addition, among the most important obstacles to commercial arbitration is the failure of the arbitrator to apply jus cogens if the arbitrator was a foreigner, not a national. Parties in a contractual relationship are afraid of resorting to arbitration, which is not an exceptional way to settle disputes. The position of the Iraqi legislator regarding neutralizing the nature of arbitration appears to have given the arbitration decision the judicial nature. Although there are similarities between commercial arbitration and commercial mediation as alternative means of settling disputes, they differ from each other in terms of the authority that the arbitrator enjoys without the commercial mediator. Moreover, in terms of the ability of the parties to the dispute to reverse the decision to refer to the mediator without the arbitrator, and with regard to the concessions to be made by the parties who resort to commercial mediation as a means of settling the dispute.